(3VeGfGJ GdeJge aj eQMdI GdJMbjb GdLfGFj (B:s (3OQGSI ebGQfI (B/s - (3Sejf, SjQhGf TcQs ((3HjQhJ (B:s (3ecJHI Rjf GdMbhbjI hGdCOHjI T(B. (3e(B. (3e(B.(3,s, 2020)
(3jYO ehVhY VeGfGJ GdeJge ef GdehGVjY GdJj fGdJ bOQG ef GdGgJeGe ef QLGd GdbGfhf hef GdegJejf HMeGjI Mbhb GdEfSGf hPdc dCQJHGW gPg GdVeGfGJ HGdCOjGf GdSeGhjI hEYdGfGJ hehGKjb Mbhb GdEfSGf GdOhdjI hGdEbdjejI hGdOSGJjQ hbhGfjf GdELQGAGJ GdLfGFjI GdJj OCHJ LejYgG Ydi GdfU hGdJCcjO Ydi JCejfgG HMbhb hVeGfGJ JMaX cQGeI GdEfSGf hJMejg hYOe GdSeGM ddOhdI HJVjjb GdNfGb Ydi gPg GdMQjI GdaQOjI EdG dVQhQI MeGjI Cef hSdGeI GdeLJeY(B.s
(3HHdjhLQGajI (B: (3UaMI (B326-342.s
Keywords: (3GdeMGceGJ GdLfGFjIs -- (3GdYQGbs; (3GdeMGceGJ GdLfGFjIs -- (3eUQs; (3GdJMbjb GdLfGFjs -- (3eUQs; (3GdJMbjb GdLfGFjs -- (3GdYQGbs; (3GdJMbjb GdLfGFjs -- (3GdYQGbs; (3GdJMbjb GdLfGFjs -- (3eUQs